Pengaruh Celebrity Worship terhadap Subjective Well-Being pada Penggemar BTS Dewasa Awal - Rahmi Fadilah Zamani; Eni Nuraeni Nugrahawati (UNISBA Press, 2022)
Abstract. BTS fans in Indonesia who are in their early adulthood describe their idol-loving behavior that leads to celebrity worship. However, since getting to know BTS, many fans have felt happiness and well-being in life or subjective well-being. This study aims to determine how much influence celebrity worship has on subjective well-being in early adult BTS fans. This study uses a quantitative method with a non-experimental causality research design with purposive sampling and data collection techniques using a questionnaire. The analysis technique uses regression test. This study involved 398 BTS fans in early adulthood. In measuring celebrity worship behavior in this study using the Celebrity Attitude Scale (CAS) from Maltby et al. (2006) with 26 valid items with a reliability coefficient (α) of 0.944. Meanwhile, to measure SWB using the Satisfaction With Life Scale (SWLS) with a total of 5 valid items with a reliability coefficient (α) of 0.824 and a Positive Negative Experience Scale (SPANE) from Diener (2003) with 12 valid items, a reliability coefficient (α) of 0.853. The results showed that there was an influence between celebrity worship and subjective well-being of 5.3%, while 94.7% was influenced by other factors. Abstrak. Penggemar BTS di Indonesia yang berusia dewasa awal menggambarkan perilaku mencintai idolanya yang mengarah pada celebrity worship. Namun, semenjak mengenal BTS banyak penggemar yang merasakan kebahagiaan dan kesejahteraan hidup atau subjective well-being. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh celebrity worship terhadap subjective well-being pada penggemar BTS dewasa awal. Penelitian ini menggunakan metode kuantitatif dengan desain penelitian kausalitas non eksperimen dengan teknik pengambilan sampel purposive sampling dan teknik pengumpulan data menggunakan kuesioner. Teknik analisis menggunakan uji regresi. Penelitian ini melibatkan 398 penggemar BTS di usia dewasa awal. Dalam mengukur perilaku celebrity worship pada penelitian ini menggunakan Celebrity Attitude Scale (CAS) dari Maltby et.al (2006) dengan 26 item valid dengan koefisien reliabilitas (α) 0,944. Sedangkan untuk mengukur SWB menggunakan Satisfaction With Life Scale (SWLS) dengan jumlah 5 item valid dengan koefisien reliabilitas (α) 0,824 dan Positive Negative Experience Scale (SPANE) dari Diener (2003) dengan 12 item valid koefisien reliabilitas (α) 0,853. Hasil penelitian menunjukkan terdapat pengaruh antara celebrity worship dan subjective well-being sebesar 5,3% sedangkan 94,7% dipengaruhi oleh faktor lain.